Do farmers pay for climate-resilient technology? Evidence from bidding experiments in eastern India - Varkey, Lisa Mariam; Chellattan Veettil, Prakashan; Patil, Vikram (Elsevier, 2023)
Using an experimental auction, we estimate demand for stress-tolerant rice varieties (STRVs) in eastern India, where frequent covariate production risks are affecting the welfare of smallholder farmers. STRVs have the potential to cope with low- to medium-intensity abiotic stresses and stabilize rice productivity in stress-prone rice ecosystems. The experiment involves a series of farmers’ decision-makings in the context of STRV seed purchase, set in an environment with minimal social frictions and improved information availability. Survival analysis, double hurdle, and sequential logit models are employed to understand farmers’ bidding and buying behavior. The results indicate that the demand for STRVs is highly elastic and is in line with reported market behavior. Willingness to pay (WTP) estimates for initial and latent buyers are coinciding, we find evidence of strategic underbidding by latent buyers in the experiment. Information asymmetry resulting from lack of awareness and previous experience in using STRVs is found to be the major reason for such decisions. Given the high elasticity of demand, STRV seed market distortion through subsidy, price cue, and an information campaign on variety characteristics and benefits could be an effective policy mix for overcoming the constraints related to price and asymmetric information and thereby increase adoption.